(untitled) (Revista Científica Integrada, 2025)
Objective: To analyze the mortality and clinical evolution of women of reproductive age (pregnant and postpartum women) with COVID-19 in Brazil during the years 2022 and 2023. Method: This is a cross-sectional, descriptive and exploratory study based on secondary data from the Brazilian Obstetric Observatory on COVID-19 (OOBr). Records of hospitalized women diagnosed with COVID-19 were included, covering demographic, clinical and gestational information. The analyses involved descriptive and bivariate statistics, considering a significance level of p<0.05. Results: Women aged 20-34 and with a high school education predominated among the cases. In terms of skin color, indigenous and black women were more vulnerable, while white women were the majority in absolute numbers. Regionally, the highest concentration was in the Southeast and the lowest in the North. The third gestational trimester had the lowest relative risk (RR=0.067; p=0.011853), followed by the puerperium (RR=0.075). Hospitalization in the ICU and the need for invasive ventilation were associated with a higher relative risk. Evolution to death was significant (RR=0.128; p=0.047329), highlighting the severity of critical cases. Conclusion: Women of reproductive age continue to be a vulnerable group to COVID-19, especially those with risk factors such as heart disease and obesity. There is a need for preventive strategies and specialized care to reduce maternal mortality. Keywords: COVID-19; Pregnancy; Postpartum Period; Women’s Health; Maternal Mortality